Penerapan Media Pembelajaran Interaktif Berbasis Flash (Studi Kasus : Mata Pelajaran Kewarganegaraan pada Siswa Kelas 4) - Yupi Kuspandi Putra; Nanda Kharisma Maulana; Muhamad Sadali; Mahpuz Mahpuz (Infotek: Jurnal Informatika dan Teknologi, 2023)
This study aims to facilitate teaching and learning activities, so as to increase students' understanding of the introduction to traditional Indonesian clothing and houses delivered by educators. The introduction of traditional clothes and houses is considered to be a very big challenge, especially for the millennial generation who are less interested in learning Indonesian culture when compared to today's modern culture. This is one of the homework for educators. In the world of education, instructional media is often overlooked for reasons of limited time to make teaching preparations and it is difficult to find the right media, so that students experience difficulties and feel bored with civics subjects. The learning method used to overcome these problems is to create interactive learning media on civics subjects with material introduction to traditional Indonesian clothing and houses. This learning media starts from the needs analysis process that will be used in making flash-based interactive learning media and creating concepts or designs according to the results of the analysis. The results to be achieved in making this interactive learning media are that students can understand the material and increase the attractiveness of student learning towards the introduction of traditional Indonesian clothing and houses, so that the teaching and learning process becomes more effective. This interactive learning media is expected to help the school, especially teachers and students, in conveying or receiving material more clearly.